MECHANISMS OF CYBERCRIMINAL ACTIVITY DEVELOPMENT DURING WARTIME (Development Service Industry Management, 2024)
The article summarizes the most common mechanisms of the development of cybercriminal activity, defines its specificity in the wartime period and the key threats facing state institutions, critical infrastructure and society as a result of the use of digital technologies for military purposes. The purpose of the study is to highlight the specifics of cybercrime in the context of military conflicts, as well as to systematize the mechanisms and tools used for cyberattacks on critical infrastructure and financial systems. In the study, using the methods of content analysis and comparative analysis, the trends and mechanisms of the development of cybercriminal activity were revealed, based on the tools of system analysis, an assessment of the interrelationships between various aspects of cybercrime (attacks on critical infrastructure, information operations, financial crimes) and their impact on the general security of the state, with the help of statistical analysis, quantitative data on cyberattacks and a comparison of the dynamics of the development of cybercrime in peacetime and wartime were carried out. The results of the analysis indicate a significant increase in the number of cyber attacks on critical infrastructure, government and military facilities, as well as the spread of disinformation campaigns. The study found that cybercriminal groups are often used as a tool of state strategy in hybrid warfare. The use of cryptocurrencies in financial crimes is one of the main trends, which complicates the fight against cybercrime due to the lack of effective regulatory mechanisms. The results of the research can be used to develop new cyber security strategies in the conditions of war, as well as to improve regulatory and legal mechanisms in the field of protection against cyber attacks and financial crimes related to cryptocurrencies.
Keywords: cybercrime; hybrid warfare; cyberattacks; critical infrastructure; cryptocurrencies; financial crimes; cybersecurity; disinformation